Development and Sustainable Tourism Strategies in Red Islands Beach, Banyuwangi Regency - Rita Parmawati; Edriana Pangestuti; Wike Wike; Rizha Hardyansah (Program Pascasarjana, 2020)
Red Islands Beach in Banyuwangi is included in the Provincial Tourism Strategic Area (KSPP). It is an example of the application on tourism management by the community, due to the existence of the community group (POKMAS). Increasing the number of tourists each year causes the need for a sustainable tourism development strategy that also involves the surrounding community to maintain environmental conditions that continue to be sustainable. So, this study aims to formulate a policy of developing sustainable marine tourism on Red Islands Beach in the Banyuwangi Regency. Data was obtained by conducting FGDs and distributing questionnaires to 10 key informants consisting of the Chairperson of Pokmas, the Homestay Manager, the Chairperson of BUMDES in Sumberagung Village, Academics, Ecoranger, Restaurant Managers, and the Management of Waste Banks. The data was analyzed using a SWOT analysis strategy to describe internal factors (IFAS) and external factors (EFAS). The results of the scoring IFAS showed the value of the Strengths (3.337) and weaknesses (2.979), while external factors showed value of opportunity (3.135) and threats (3.224). The strategy that can be applied based on this analysis is Concentric Diversification Strategies. These strategies focus on adding products and services related to the tourism destination, which uses Weakness and Threat (W-T) components. This strategy will overcome weaknesses and minimize threats on Red Islands Beach. Some points that can be carried out in this strategy are increasing human resources, providing education to the community, and negotiating with other interested parties in the Marine Tourism Region of Red Islands Beach.Keywords: Red Island Beach, sustainable tourism, SWOT.Â